Socialization of the Process of Making Chicken Meatballs With the Addition of Red Spinach Extract (Amaranthus tricolor) in Paya Ue Village, Aceh Besar - Ika Rezvani Aprita; Chairil Anwar; Irhami Irhami (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2022)
The purpose of the Community Service Activity is to convey knowledge to the community about alternative uses of vegetables, especially red spinach, the process of processing chicken meat into processed food products in the form of meatballs, explaining the nutritional value of red spinach which is very beneficial for body health and can be a skill for rural communities, especially PKK mothers in providing healthy and nutritious processed food. In Paya Ue Village, Blang Bintang District, Aceh Besar. The Community Service Team consisting of several lecturers assisted by several students conducted a survey and analysis of the situation in the village so that problems in the village could be identified. The problem found is still a lack of understanding of alternative uses of vegetables, especially red spinach (Amaranthus Tricolor), as a vegetable that has high antioxidant value, and can be used in the processing of chicken meat into meatballs. The expected result of the village Community Service activity is that the village community understands the process of processing chicken meat into meatballs with the addition of red spinach extract, and is able to prepare other processed chicken meat so that it has high nutritional value.